The Book of Direction to the Duties of the Heart. - Pakuda, Bahya Ben Joseph Ibn (Littman Library of Jewish Civilization, The, 1973)
Bahya Ibn Pakuda was born c. 1050, and lived for some time in Saragossa in Spain. His major work was written in Arabic, but it is most well-known by its Hebrew title Hovot ha-Levavot (Duties of the Heart). It enjoyed enormous popularity and was reprinted many times. In the book Bahya investigates the motivation of Jewish practice and embarks on a philosophical enquiry into the nature of God, religion, and man. He was very much influenced by the Neoplatonism of his age, as well as by the Muslim mystics. This edition by Menahem Mansoor is the first translation of the work from the original Arabi.